1999
DOI: 10.1111/1467-7687.00077
|View full text |Cite
|
Sign up to set email alerts
|

Animacy and propulsion in infancy: Tracking, waving and reaching to self‐propelled and induced moving objects

Abstract: Infants from 16 to 20 weeks were videotaped while being presented with objects traversing a 60 cm distance. Four conditions were tested: (1) induced movement, holding the object; (2) induced movement, pushing the object; (3) selfpropelled mechanical movement, object moving by an internal clockwork; (4) self-propelled biological movement, animate object moving by internal impulse. In tracking, the self-propelled but inanimate and mechanically moving object with the more straight and predictable trajectory attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We called this priority the standard toy choice pattern because it showed in both men and women – parent or not – and in men in an even more pronounced fashion than in women. This result confirmed our expectation that life-like figures and cuddly toys would be less interesting (Crichton and Lange-Küttner, 1999; Servin et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We called this priority the standard toy choice pattern because it showed in both men and women – parent or not – and in men in an even more pronounced fashion than in women. This result confirmed our expectation that life-like figures and cuddly toys would be less interesting (Crichton and Lange-Küttner, 1999; Servin et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…As such, neither personality feature is positive or negative. Previous research showed that as soon as infants can reach for toys at 4–5 months of age, they prefer mechanically moving toys because they are more predictable than live animals and more interesting than cuddly toys (Crichton and Lange-Küttner, 1999). Moreover, recent research showed no looking preferences for sex-specific toys and faces in 4- and 5-months old infants (Escudero et al, 2013), thus, these authors suggested that there is no innate sex-related toy choice bias in the infants themselves.…”
Section: Discussionmentioning
confidence: 99%
“…They track objects with self-propelled movement (Crichton & Lange Kuettner 1999). They also show more interest in the kinematic patterns of point-light displays of a person walking than of random movement (Bertenthal et al 1984).…”
Section: (B) From Age 3 Yearsmentioning
confidence: 99%
“…Not only eye movements but also other forms of biological motion seem to have a privileged status in attracting infants' attention at an extremely early age. They track objects with self-propelled movement (Crichton & Lange Kuettner 1999). They also show more interest in the kinematic patterns of point-light displays of a person walking than of random movement (Bertenthal et al 1984).…”
Section: (G) From Three Months Of Agementioning
confidence: 99%
“…However, while perception is a crucial ability which becomes refined even at a later age (Lange-Kiittner, 2000), action and interaction seems to provide the major incentive for the infant to gain relevant knowledge about the object world outside his or her own body (Crichton and Lange-Kiittner, 1999). The maturation of the frontal lobes in the first year of life appears to start very early, already with the beginning of goal-directed co-ordinated reaching towards objects at about four to five months (Diamond, 1991;Von Hofsten and Fazel-Zandy, 1984).…”
mentioning
confidence: 99%